2021
DOI: 10.3389/fgwh.2021.614310
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: “Crisis Within the Walls”: Rise of Intimate Partner Violence During the Pandemic, Indian Perspectives

Abstract: The ongoing coronavirus disease 2019 pandemic has been a social “un-equalizer,” besides being a global health threat. Gender inequality has been globally prominent during the outbreak and the consequent lockdown. Although domestic abuse and intimate partner violence have increased due to chronic entrapment, overcrowding in families, enhanced substance use, distorted relationship dynamics, travel restrictions, and reduced healthcare access, coercive sexual practices have also been on the rise. In low- and middl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…Simultaneously, providers of GBV prevention and response services have been tasked with providing quality care in the face of significant resource challenges, slowed coordination, and minimal protections for their own physical and mental health. Similarly to other studies that have documented challenges in GBV service provision during the COVID-19 pandemic [ 18 , 32 , 40 , 45 , 46 , 47 , 48 , 49 ], findings from this study highlight the inordinate challenges faced by providers (lack of funding, PPE shortages, limited technological infrastructure, and poor cross-sectoral communication and collaboration) and the exacerbation of poverty and adversity faced by survivors. Efforts to strengthen the GBV prevention and response system should include, among other strategies, strengthening partnerships and critical infrastructure for GBV prevention/response, public transportation, and telecommunications, particularly among rural areas and Indigenous populations.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Simultaneously, providers of GBV prevention and response services have been tasked with providing quality care in the face of significant resource challenges, slowed coordination, and minimal protections for their own physical and mental health. Similarly to other studies that have documented challenges in GBV service provision during the COVID-19 pandemic [ 18 , 32 , 40 , 45 , 46 , 47 , 48 , 49 ], findings from this study highlight the inordinate challenges faced by providers (lack of funding, PPE shortages, limited technological infrastructure, and poor cross-sectoral communication and collaboration) and the exacerbation of poverty and adversity faced by survivors. Efforts to strengthen the GBV prevention and response system should include, among other strategies, strengthening partnerships and critical infrastructure for GBV prevention/response, public transportation, and telecommunications, particularly among rural areas and Indigenous populations.…”
Section: Discussionsupporting
confidence: 74%
“…Some Guatemalans were able to effectively engage with digitized GBV services. However, it has been globally reported that survivors without access to technology are systematically excluded from digitized GBV services [ 18 , 41 , 48 ]. DDs and limited access to transportation operated in similar ways to reduce reporting and service access.…”
Section: Discussionmentioning
confidence: 99%
“…For example, even though during the ongoing unprecedented COVID-19, intimate partner violence and marital discord have been on rise and we have all faced distress calls in our helplines, explicit discussion about marital rape in social media, or academic literature has been sparse. 12,13 The Indian Scenario India is one of the 36 countries that has still not criminalized marital rape. Over the years, the exemption to an unwilling sexual intercourse between husband and wife (above 15 years of age) in IPC Section 375 has been widely debated and argued against.…”
Section: Public Perceptions and Legal Ambiguitymentioning
confidence: 99%
“…During the pandemic, the health systems were overwhelmed, leaving women with limited access to the prevention of GBV services. The focus shifted to providing essential services and preventing the spread of COVID-19 ( 21 – 23 ). The pandemic also challenged GBV service provision and program implementation at the community level as many organizations prioritized providing first-line COVID-19 relief services.…”
Section: Gender-based Violence Programming In Times Of Covid-19mentioning
confidence: 99%
“…There has been a reduction in financial security risks increasing gaps in the intra-household distribution of resources biased towards men and boys, which could further negatively impact women in the household ( 34 ). The existing gender digital divide ( 35 ) leads to not having access to phones, computers, or internet services, or being able to use them safely at home for communication, makes them even more excluded as they have to depend upon their husbands, fathers, or brothers for using the mobile phones and internet services ( 23 ). Additionally, those with access to phones and internet services, experienced technology-based violence during the pandemic.…”
Section: Challenges For Gender-based Programming In Times Of Covid-19...mentioning
confidence: 99%